2022
DOI: 10.3390/ma15228197
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructures and Mechanical Properties of Nb-V Alloyed Ultra-High Strength Hot Stamping Steel in Austenitizing Process

Abstract: Clarifying the influence of Nb and V microalloying on the ultra-high strength hot stamping steel (UHSHSS) and exploring appropriate process parameters are the basis for effectively regulating properties of the final product. In this study, the effects of different austenitizing temperatures and holding times on the phase transitions, grain sizes and mechanical properties of 22MnB5NbV with Nb and V alloyed are studied by using JMatPro thermodynamic calculations and experiments. By comparing with 22MnB5 without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Regardless of the steel type, the increased addition of microalloying elements can contribute, to varying degrees, to the structural refinement of martensite considering prior austenite grain size. In some cases, this can lead to an improvement in the strength–ductility balance, such as with Nb- and Mo-microalloyed 22MnB5 steel [ 49 ], Ti- and Nb-microalloyed 22MnB5 steel [ 50 ], Ti-, Nb- and V-microalloyed 22MnB5 steel [ 51 ], Ta-microalloyed 22MnB5 steel [ 52 ], and Nb- and Mo-microalloyed 38MnB5 steel [ 53 ]. However, simply increasing the content of microalloying elements cannot necessarily achieve strength–ductility synergy.…”
Section: Traditional Mn-b Steelsmentioning
confidence: 99%
“…Regardless of the steel type, the increased addition of microalloying elements can contribute, to varying degrees, to the structural refinement of martensite considering prior austenite grain size. In some cases, this can lead to an improvement in the strength–ductility balance, such as with Nb- and Mo-microalloyed 22MnB5 steel [ 49 ], Ti- and Nb-microalloyed 22MnB5 steel [ 50 ], Ti-, Nb- and V-microalloyed 22MnB5 steel [ 51 ], Ta-microalloyed 22MnB5 steel [ 52 ], and Nb- and Mo-microalloyed 38MnB5 steel [ 53 ]. However, simply increasing the content of microalloying elements cannot necessarily achieve strength–ductility synergy.…”
Section: Traditional Mn-b Steelsmentioning
confidence: 99%
“…Wu et al studied the evolution of microstructure in the heat-affected zone of a 1.2 mm-thick Q&p980 steel under different peak temperature conditions, they found there is a single phase of martensitic and the volume percentage of retained austenite decreases from 13% to 2% when the peak temperature increases from 300°c to 1350°c [15]. Regarding the combined effects of high temperature and time on material microstructure [16][17][18][19], liu et al studied the influence of austenitization temperature and holding time on grain size in 1.5 mm-thick 22MnB5nbv steel, and found that there is a proportional relationship between the grain size and temperature, as well as the grain size and holding time extension [17]. li et al investigated the effect of holding time on the microstructure of 1.6 mm-thick B1500HS steel after heating at 930°c, and observed a reduction in the volume fraction of martensite with increasing holding time [18].…”
Section: Introductionmentioning
confidence: 99%
“…The development and application of ultra‐high strength hot‐forming steel are one of the significant measures to realize automobile lightweight due to its various advantages such as high dimensional accuracy, less rebound cracking, and long lifetime of molds. [ 1–4 ] Compared with the conventional process, the thin slab casting and rolling (TSCR) process has significant advantages such as high efficiency, energy saving, and low cost, [ 5–7 ] and has become one of the main trends for the future production of ultra‐high strength hot‐forming steels for automotive applications. [ 8–10 ] However, compared with the traditional continuous casting process, the TSCR process does not undergo the phase transformation process of γ → α → γ, [ 5–7 ] and the austenite grains before rolling are even as high as 500–2000 μm, [ 6,11,12 ] which will lead to significant fluctuations in the final product properties.…”
Section: Introductionmentioning
confidence: 99%